A Study of Conceptual Framework of Blind Recruitment in Current Business Scenario - Ramakrishnan Vivek (University of Jaffna, 2018)
This is a conceptual paper is to study the concept of Blind recruitment, usage of blind recruitment, forms of recruitment in the organization and the advantages and disadvantages of Blind recruitment. Recruitment is the method of searching and hiring the best- qualified aspirant from inside or outside of a business for a job opening, in a timely and cost-effective manner. It is absolutely crucial for businesses to hire the right people, with the right skills, the right knowledge, right attributes, at the right time, for the right job. The recruitment and selection process has become one of the key processes determining the success of an organization. At the present, the practice of issuing a vacant position and applying for a job via the website has increased massively but ensuring diversity among workplace still questionable in a major organization. Blind recruitment is the solution of removing all drawbacks what is in the current recruitment systems. One of the most innovative trends using by in a developed country that method called Blind recruitment. Researcher worked on this study/paper based on previous online sources, HR blogs, Journals and books. The main purpose of this paper is to broaden the research on the recruitment practices, with focus on Blind recruitment practices in addition with that this paper discusses the concept, nature, problems, benefits, methods, and trends and conditions for effective blind recruitment.
Keywords: Recruitment and selection; Blind Recruitment; emerging trends of Recruitment